Dietary patterns and sustainable lifestyles: a multicenter study from Latin America and Spain - Parra Soto, Solange Liliana (2025)
Food systems interact through multiple dimensions including food security, nutrition, and planetary health. This study aims to associate different dietary patterns with sustainable lifestyles in Latin America and Spain. This was an observational, analytical, multicenter, cross-sectional survey study, with a total of 6412 participants. A self-administered questionnaire was developed in an online format in the Google Docs interface. The questionnaire was divided into sections: (1) sociodemographic background: country of residence, age, sex, educational level, socioeconomic aspects, and place of residence; (2) body mass index classification; (3) dietary patterns (Western, vegetarian, vegan, ketogenic, Mediterranean, prudent, or paleolithic diets); and (4) the Sustainable Lifestyles Survey. Multivariate models were applied to adjust for potential confounding factors. The mean age of the participants was 35.2 years (SD 12.7). The majority of participants identified their dietary pattern as omnivorous (41.5%), followed by the Western diet (21.7%) and the Mediterranean diet (12.7%). Plant-based, vegan (β: 14.90; 95% CI: 9.75–20.05), and lacto egg (β: 12.08; 95% CI: 8.57–15.58) diets are significantly associated with a higher sustainability score compared to an omnivorous diet. In contrast, a Western diet is inversely associated (β: −5.63; 95% CI: −7.20 to −4.06). Finally, a vegan (Sub-score 1: β: 6.19; 95% CI: 4.43–7.96) diet is consistently associated with higher levels of sustainability in all areas assessed. In contrast, the Western diet shows a significant negative association with sustainability in all subcomponents assessed. Conclusions: Plant-based dietary patterns were shown to be associated with sustainable lifestyles, with the vegan diet having the greatest association, while the Western dietary pattern was inversely associated.